Resource Allocation Algorithm in Uplink OFDMA-Based Decode-and-Forward Relay Systems with Proportional Rate Constraints - Cuiru Zhao; Youming Li; Bin Chen; Ting Zou; Xiaoqing Liu (Dianxin kexue)
For orthogonal frequency division multiple access-based decode-and-forward（OFDMA-DF）relay uplinks communication system，a new algorithm with proportional fairness constraints of users’ rate was presented.The new algorithm was divided into two steps.Firstly，under equal power distribution，the user with the lowest proportional capacity had the option to pick which subcarrier and relay to use.Then，based on this basis，power allocation was optimized on subcarriers and the power allocation results were given.Analysis results demonstrate that the new algorithm can not only obtain high system capacity，but also guarantee fairness between users.